2021
DOI: 10.1002/jmv.27473
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and molecular characterization of human respiratory syncytial virus and human adenovirus among children in Ado‐Ekiti, Nigeria

Abstract: In children, the respiratory syncytial virus and adenovirus majorly cause acute respiratory infections. The study evaluated the seroprevalence and conducted the molecular characterization of human respiratory syncytial virus (HRSV) and human adenovirus (HAdV) among children. Venous blood, nasopharyngeal, and oropharyngeal swabs were collected from children presenting with acute respiratory infections in a tertiary health facility in Ado-Ekiti, Nigeria. A serological investigation was carried out on the sera sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…RSV is among the frequent causative agent of severe RTIs in infants and children with 76% of children being re-infected by the second year of life (Faneye et al, 2014). The seroprevalence of RSV IgM was 40% among the tested subjects and is similar to an earlier study by Sulaiman et al (2017) (Idris and Kolawole, 2022).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…RSV is among the frequent causative agent of severe RTIs in infants and children with 76% of children being re-infected by the second year of life (Faneye et al, 2014). The seroprevalence of RSV IgM was 40% among the tested subjects and is similar to an earlier study by Sulaiman et al (2017) (Idris and Kolawole, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…Fever was significantly associated with RSV IgG (p=0.025) and PIV IgG (p=0.039). A similar study also reported a significant association (p<0.05) between fever and RSV IgG (Idris and Kolawole, 2022).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations